2003
DOI: 10.1002/ajim.10256
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide exposure and women's health

Abstract: Gender-sensitive research is needed to properly address the study of women's pesticide exposures and related adverse outcomes. A better understanding of potential gender-environment and sex-environment interactions related to pesticide exposure and health effects in women is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 61 publications
3
50
0
3
Order By: Relevance
“…Females involved in agricultural work reported a higher percentage of adverse outcomes of pregnancy (abortion, stillbirth and congenital anomalies) compared to females not engaged in agriculture, which agrees with other studies [22][23][24][25][26]. The intricate processes of the menstrual cycle, ovum production, fertilization, implantation, growth and development of the foetus may be particularly susceptible to low-dose exposures to endocrine disruptors.…”
Section: Helping In Farming Operationssupporting
confidence: 87%
“…Females involved in agricultural work reported a higher percentage of adverse outcomes of pregnancy (abortion, stillbirth and congenital anomalies) compared to females not engaged in agriculture, which agrees with other studies [22][23][24][25][26]. The intricate processes of the menstrual cycle, ovum production, fertilization, implantation, growth and development of the foetus may be particularly susceptible to low-dose exposures to endocrine disruptors.…”
Section: Helping In Farming Operationssupporting
confidence: 87%
“…Labreche and Goldberg [1997] hypothesized a plausible mechanism for breast cancer carcinogenicity of organic solvents through their hormonal properties. Another group of chemicals that can act through the same mechanism in increasing risk of breast cancer are a number of pesticides [Garcia, 2002]. Indeed, almost 5% of the breast cancer patients in our study reported an exposure to pesticides.…”
Section: Discussionmentioning
confidence: 96%
“…There has been expressed concern about female farmers spraying and the need for more data on gender differences in response to pesticides exposure [1,24]. Very few studies look at both genders in relation to pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies have shown that gender and age can modify the effect of number of times sprayed in relation to acute pesticide symptoms [13,19,24,25]. Therefore we tested for interactions with gender and age, with both the interaction term and the main effects in the analyses.…”
Section: Methodsmentioning
confidence: 99%